O Entrelaçamento Entre Ego E Ego-Visto Em Sartre: Análise Da Origem Dos Conceitos - Erculino, Siloe Cristina Do Nascimento [UNIFESP] (2018)
In His Work The Transcendence Of The Ego, Sartre Defined The Psychic Ego As A Transcendent Object Constituted By Impure Reflection, And In His Work, Being And Nothingness, He Stated That Our Ego-Seen (Ego-Regardé) Is Composed By The Other In The Dynamics Of Viewing. We Propose To Think About The Extent In Which These Two Concepts Are Related, Seeking To Understand The Theme From Its Origins In Husserl's Theory. Sartre Explained The Concept Of Intentionality, The Pillar Upon Which He Built His Theory, In His Article L'intentionnalité, Later In The Transcendence Of The Ego, He Denoted The Conception Of Ego As A Transcendent Object And, In Being And Nothingness, He Demonstrated The Encounter With The Other While Subjectivity, In Which My Ego-Seen (Being-For-Others) Is Constituted In The Dynamics Of Viewing. In The First Moment Of This Dynamics, The Other Seizes Me, As An Object; Therefore, It Is Subject That Constitutes My Ego-Seen In The World. In The Second Moment, I Seize The Other As An Object Seen In The Wo